Diversity and Super-Diversity : Sociocultural Linguistic Perspectives - Wegner, Jeremy; Ikizoglu, Didem; De Fina, Anna (Book collections on Project MUSE., 2017)
Sociocultural linguistics has long conceived of languages as well-bounded, separate codes. But the increasing diversity of languages encountered by most people in their daily lives challenges this conception. Globalization has accelerated population flows, so that cities are now sites of encounter for groups that are highly diverse in terms of origins, cultural practices, and languages. New media technologies invent communicative genres, foster hybrid semiotic practices, and spread diversity as they intensify contact and exchange between peoples who often are spatially removed and culturally different from each other. Diversity--even super-diversity--is now the norm. In response, recent scholarship complicates traditional associations between languages and social identities, emphasizing the connectedness of communicative events and practices at different scales and the embedding of languages within new physical landscapes and mediated practices. This volume takes stock of the increasing diversity of linguistic phenomena and faces the theoretical-methodological challenges that accounting for such phenomena poses to sociocultural linguistics.